The role of risk mitigation actions in engineering projects: An empirical investigation. Issue 6 (10th September 2022) - Shafqat, Ali; Oehmen, Josef; Welo, Torgeir; Ringen, Geir
Abstract: Engineering‐heavy new product development (NPD) projects face unplanned design iterations, which can cause failure in terms of missed targets for cost, schedule, quality, and customer satisfaction. These unplanned design iterations can be understood as the occurrence of a specific category of engineering project risks. As a result, companies employ structured actions to mitigate these risks in projects. However, even with such strategies in place, projects can still struggle to achieve their targets. This study aims to explore how companies employ risk mitigation actions to manage risks in engineering‐based NPD projects. To investigate this topic, a survey of employees in the aerospace and defense industries was conducted. We analyzed the responses using statistical methods. The results indicate that risk mitigation actions are used according to thematic clusters, in line with our findings from the literature. Furthermore, the selected mitigation measures show collective explanatory power for handling engineering project risks, suggesting that while some projects that employ mitigation actions may still fail, their use of such measures does still reduce the overall impact of risks. Interestingly, the results of the statistical analysis show no significant difference in the employment of risk mitigation actions in engineering‐based NPD projects, whether they employ waterfall or agile NPD methods, or a mixture of both. These results suggest that companies should consider all classes of risk mitigation actions to manage engineering project risks. On this basis, the wider contextualization of individual mitigating actions should be taken into account when planning risk mitigation for engineering‐based NPD projects.